2023
DOI: 10.1080/14786419.2023.2180504
|View full text |Cite
|
Sign up to set email alerts
|

Pentacyclic triterpenoids from the stem of Grewia bracteata Roth demonstrate promising inhibition on tumour cells

Abstract: Grewia bracteata Roth stem was investigated for its anticancer potential for the first time.Initially, polarity-guided extracts from three solvents were screened on HeLa, HCT-116 and MCF-7 tumours cells. The results revealed that ethyl acetate extract (GSE) significantly (p<0.05) inhibited HeLa, HCT-116 and MCF-7 cells with respective IC50 values of 30.58, 14.26 and 22.91 µg/ml. GSE inhibited HCT-116 cells with 6-and 21-folds higher than hexane (GSN) and methanol (GSM) extracts, respectively. Hence, column chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…3 In addition, Grewia significantly contributed to the food processing sector, particularly in the productions of preserves, fruit juices, and teas. 4 It is found that plants of this genus served as a reservoir of diverse phytochemicals, 4 including flavonoids, 3,5 alkaloids, 3,6,7 triterpenoids, 3,8 phenols, 3,8,9 polysaccharides, 10,11 and others. 7,1216 These compounds manifest a spectrum of bioactivities, such as antioxidant, anti-inflammatory, anticancer, antidiabetic, antibacterial, antispasmodic, antiviral, antimicrobial, and antimalarial properties.…”
Section: Introductionmentioning
confidence: 99%
“…3 In addition, Grewia significantly contributed to the food processing sector, particularly in the productions of preserves, fruit juices, and teas. 4 It is found that plants of this genus served as a reservoir of diverse phytochemicals, 4 including flavonoids, 3,5 alkaloids, 3,6,7 triterpenoids, 3,8 phenols, 3,8,9 polysaccharides, 10,11 and others. 7,1216 These compounds manifest a spectrum of bioactivities, such as antioxidant, anti-inflammatory, anticancer, antidiabetic, antibacterial, antispasmodic, antiviral, antimicrobial, and antimalarial properties.…”
Section: Introductionmentioning
confidence: 99%